Accounting Challenges for Semi-Autonomous Revenue Agencies in Developing Countries - Terkper, Seth (IMF Working Papers; Working Paper ;, 2008)
The paper discusses the improvements which a semi-autonomous revenue agency (SARA) must make to its records to meet fiscal and financial accounting obligations. SARAs are legal entities, such as a service or a department, which are required to prepare accrual records that may diverge from a treasury's cash accounting records. Their records reflect revenues generated; budget funds for generating the revenues; and material programs administered for other agencies. The accounting records and financial statements (income statement, balance sheet and cash flow statement) must conform to generally-accepted accounting principles (GAAPs) or standards such as the International Public Sector Accounting Standards (IPSAS) of the International Federation of Accountants (IFAC)-and to the treatment of operating, investment and financing activities in the Government Finance Statistics (GFS) Manual.